Theoretical investigations of novel Janus Pb2SSe monolayer as a potential multifunctional material for piezoelectric, photovoltaic, and thermoelectric applications. Issue 37 (31st August 2021) - Zhang, Fusheng; Qiu, Jian; Guo, Haojie; Wu, Lingmei; Zhu, Bao; Zheng, Kai; Li, Hui; Wang, Zeping; Chen, Xianping; Yu, Jiabing
Abstract : Two-dimensional Janus Pb2 SSe monolayer, due to its unique antisymmetric structure as well as excellent electronic, optical and piezoelectric properties, exhibit great prospects in multifunctional energy applications. Abstract : Two-dimensional Janus nanomaterials, due to their unique electronic, optical, and piezoelectric characteristics resulting from the antisymmetric structures, exhibit great prospects in multifunctional energy application to alleviate the energy crisis. Monolayer Janus Pb2 SSe, with a black phosphorus-like structure and an indirect band gap of 1.59 eV as well as high carrier mobility (526–2105 cm 2 V −1 s −1 ), displays outstanding potentials in the energy conversion between nanomechanical energy, solar energy, waste heat, and electricity, which has been comprehensively studied utilizing DFT-based simulations. The research results reveal that monolayer Pb2 SSe not only possesses giant in-plane piezoelectricity of d 11 = 75.1 pm V −1 but also superhigh out-of-plane piezoelectric coefficients ( d 31 = 0.5 pm V −1 and d 33 = 15.7 pm V −1 ). Meanwhile, by constructing Pb2 SSe bilayers, the out-of-plane piezoelectric coefficients can be significantly enhanced ( d 31 = 19.2 pm V −1 and d 33 = 194.7 pm V −1 ). In addition, owing to the small conduction band offset, suitable donor band gap and excellent light absorption capability in the Pb2 SSe/SnSe (Pb2 SSe/GeSe) heterostructure, the power conversion efficiencies were calculated to be up to 20.02% (Pb2 SSe/SnSe) and 19.28% (Pb2 SSe/GeSe), making it a promising candidate for solar energy collection. Furthermore, from the thermoelectric electron and phonon transport calculations, it can be found that the Pb2 SSe monolayer is an n-type thermoelectric material with ultrahigh ZT = 2.19 (1.52) at room temperature, which can be traced back to its ultralow κ L = 0.78 (0.99) W m −1 K −1, and superhigh PF = 10.18 (8.25) mW m −1 K −2 along the x ( y ) direction at the optimal doping concentration at 300 K. The abovementioned versatile characteristics in the Janus Pb2 SSe monolayer, along with its comprehensive stabilities (energy, dynamic, thermal, and mechanical stabilities), highlight its potential in clean energy harvesting.